2017
DOI: 10.4162/nrp.2017.11.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Increased glucose metabolism and alpha-glucosidase inhibition inCordyceps militariswater extract-treated HepG2 cells

Abstract: BACKGROUND/OBJECTIVESRecent living condition improvements, changes in dietary habits, and reductions in physical activity are contributing to an increase in metabolic syndrome symptoms including diabetes and obesity. Through such societal developments, humankind is continuously exposed to metabolic diseases such as diabetes, and the number of the victims is increasing. This study investigated Cordyceps militaris water extract (CMW)-induced glucose uptake in HepG2 cells and the effect of CMW treatment on glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
1
13
0
2
Order By: Relevance
“…Our study showed that methanolic extract of C. militaris did not inhibit the activity of α-amylase (Table 1), while it had inhibitory potential on α-glucosidase. A recent study showed that water extract of C. militaris had inhibitory activities on α-glucosidase with values of 45.77% with 0.1 mg/mL, 54.76% with 0.25 mg/mL, 58.74% with 0.5 mg/mL, and 60.5% with 1.0 mg/mL (Kim et al, 2017). The organic acid we found previously in higher amounts in C. militaris was citric acid 7.97 g/100 g (Bizarro et al, 2015).…”
Section: Mushroom Species Yield Of Extracts (%) α-Amylase Inhibition;mentioning
confidence: 99%
“…Our study showed that methanolic extract of C. militaris did not inhibit the activity of α-amylase (Table 1), while it had inhibitory potential on α-glucosidase. A recent study showed that water extract of C. militaris had inhibitory activities on α-glucosidase with values of 45.77% with 0.1 mg/mL, 54.76% with 0.25 mg/mL, 58.74% with 0.5 mg/mL, and 60.5% with 1.0 mg/mL (Kim et al, 2017). The organic acid we found previously in higher amounts in C. militaris was citric acid 7.97 g/100 g (Bizarro et al, 2015).…”
Section: Mushroom Species Yield Of Extracts (%) α-Amylase Inhibition;mentioning
confidence: 99%
“…Compounds 2, 6, and 7 are the main compound with higher α-glucosidase-inhibitory activity than that of acarbose (the positive control). This finding suggested that these compounds may have antidiabetic efficacy and may be further developed as a drug supplement following additional investigation of their activities and safety (Kim et al, 2017).…”
Section: α-Glucosidase Inhibitory Effect Of the Isolated Compoundsmentioning
confidence: 93%
“…Cordyceps are found to regulate and also lower the blood sugar levels by improving metabolism of glucose and conserving hepatic glycogen (Zhao et al 2002;El-Hagrassi et al 2020). Cordyceps can increase secretion of glucokinase and hexokinase which are glucose regulating enzymes secreted by the liver (Kim et al 2017). Polysaccharides are the key player in showing the hypoglycaemic activity of Cordyceps.…”
Section: Hypoglycemic and Hypocholesterolemic Effectmentioning
confidence: 99%